Өрмийн шаврын химийн найрлагын судалгаа - Д.Ундармаа; Р. Уламбаяр (Geological Issues, 2023)
Recent years Mongolia is conducting high activities in mining and mineral resource sector so that necessity of drillings is growing accordingly in every year. Therefore usage of chemical reagents for cleaning the drilling well is being increasingly required in the sector. Many of Mongolian drilling companies apply imported high expensive chemical reagents and elaborated clay powders for their cleaning applications of the drilling wells. In the drillings of solid and fluid mineral resources, properties and abilities of drilling mud stabilizing the wall of the well and detaining the grains are more especial and preferable than other drilling fluids’. So, in some cases, our drilling companies would also use domestic drilling mud directly from nature in addition to the imported products. However, direct natural mud application causes some technical issues that chemical and physical properties of the natural mud are not met to the requirements of technology and technical apparatus using in the drillings. Mongolia has several montmorillonite mud deposits which can be applied for kinds of applications including the cleaning application of the drillings. Therefore the country and specialists in the sector are considerably paying attention on the importance of the natural mud research including techno-economical possibilities to establish industry, and physical and chemical processing technologies that can be used in the industry. So, purpose of my research work would be focused on techno-economical possibility of the drilling mud processing industry particularly procurement of the natural mud for making good quality drilling mud by applying recent advanced chemical and physical technologies in tire world level. Necessarily the research work focuses on technical processing to improve the chemical and physical properties of the natural mud for processing and making drilling mud.